PENGARUH METODE LATIHAN DRILL TERHADAP KETERAMPILAN PASSING BAWAH PADA EKSTRAKULIKULER BOLA VOLI DI SMPN 15 JAKARTA - Wirra Yudishtira; Setio Nugroho; Rhama Nurwansyah Sumarsono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the drill training method on underhand passing skills in volleyball extracurricular activities at SMPN 15 Jakarta. This study applies the pre-experiment method. Pre-experiment, in the context of quantitative research, is defined as a very complete research approach, where the method meets all the criteria for testing the relationship of cause and effect. In the context of this study, a quantitative approach is used to determine the effect of the drill training method on underhand passing skills in volleyball extracurricular activities at SMPN 15 Jakarta. drill training method. The average (mean) score of students during the pretest was 66.85, increasing to 81.38 in the posttest. This indicates an increase of 14.53 points. Second, the results of the normality test show that the pretest and posttest data are normally distributed with Shapiro–Wilk significance values ​​of 0.427 for the pretest and 0.056 for the posttest, respectively. Furthermore, the results of the homogeneity test using Levene's Test also showed that the data had the same variance or Third, the results of the paired t-test (Paired Sample T-Test) showed a significant difference between the pretest and posttest results with a calculated t value of 32.757 and a significance value (Sig. 2-tailed) of 0.000 (<0.05). Thus, it can be concluded that the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted to be homogeneous, with a significance value (Sig.) of 0.282 (>0.05). Overall, the results of this study prove that the drill training method has a significant effect on improving volleyball underhand passing skills. Thus, this training method can be used as an effective learning alternative for physical education teachers and extracurricular coaches to improve students' basic technical abilities, especially in volleyball.